Profiling by image registration reveals common origin of Annelid mushroom bodies and vertebrate pallium - Tomer, Raju; Denes, Alexandru S.; Tessmar-Raible, Kristin; Arendt, Detlev (Cell, 2010)
Summary The evolution of the highest-order human brain center, the “pallium” or “cortex,” remains enigmatic. To elucidate its origins, we set out to identify related brain parts in phylogenetically distant animals, to then unravel common aspects in cellular composition and molecular architecture. Here, we compare vertebrate pallium development to that of the mushroom bodies, sensory-associative brain centers, in an annelid. Using a newly developed protocol for cellular profiling by image registration (PrImR), we obtain a high-resolution gene expression map for the developing annelid brain. Comparison to the vertebrate pallium reveals that the annelid mushroom bodies develop from similar molecular coordinates within a conserved overall molecular brain topology and that their development involves conserved patterning mechanisms and produces conserved neuron types that existed already in the protostome-deuterostome ancestors. These data indicate deep homology of pallium and mushroom bodies and date back the origin of higher brain centers to prebilaterian times.